Myeloid sarcoma with RBM15::MRTFA (MKL1) mimicking vascular neoplasm - Gündoğdu, Fatma; Agaimy, Abbas; Aytaç, Selin; Hazar, Volkan; Üner, Ayşegül; Kösemehmetoğlu, Kemal (Virchows Archiv, 2024)
Extramedullary involvement of acute myeloid leukemia (AML), aka myeloid sarcoma, is a rare phenomenon in acute megakaryoblastic leukemia with RBM15:: MRTFA(MKL1) fusion, which might mimic non-hematologic malignancies. A 7-month-old infant presented with leukocytosis, hepatosplenomegaly, multiple lymphadenopathies, and a solid mass in the right thigh. Initially, the patient was diagnosed with a malignant vascular tumor regarding the expression of vascular markers from the biopsy of the right thigh lesion that was performed after the inconclusive bone marrow biopsy. The second bone marrow biopsy, which was performed due to the partial response to sarcoma treatment, showed hypercellular bone marrow with CD34 and CD61-positive spindle cell infiltration and > 20% basophilic blasts with cytoplasmic blebs. RNA sequencing of soft tissue biopsy revealed the presence of RBM15::MRTFA(MKL1) fusion. Based on these findings, myeloid sarcoma/AML with RBM15::MRTFA(MKL1) fusion diagnosis was made. AML with RBM15::MRTFA(MKL1) fusion can initially present as extramedullary lesions and might cause misdiagnosis of non-hematologic malignancies.
CRIS-Team Scopus Importer:2024-05-17
Keywords: Acute megakaryoblastic leukemia; Children; Malignant mesenchymal tumor; Myeloid sarcoma; RBM15::MRTFA(MKL1) fusion; Vascular neoplasm